Analyzing 'Himawari No Yakusoku' in 'Stand by Me Doraemon' through film soundtrack and communication theories - Yefya Bako; Dandi Hafiddin; Feysya Salsabila Ramadhani (Interlude: Indonesian Journal of Music Research, Development, and Technology, 2024)
This study examines the impact of the song "Himawari No Yakusoku" on the narrative and emotional complexity of "Stand by Me Doraemon" using film soundtrack theory and film communication theory. The focus of this inquiry is the incorporation of music into cinematic storytelling in order to elicit emotions and strengthen narrative ideas. The significance of this study arises from the increasing acknowledgment of music's pivotal role in the film, requiring a more profound comprehension of how soundtracks enhance the viewer's experience. This research used a qualitative analytical methodology to investigate the structural components of the song, encompassing its introduction, verses, pre-chorus, chorus, instrumental section, and outro. The analysis utilizes theoretical frameworks from prominent works in the field of film music studies, such as Claudia Gorbman's theory on narrative film music, Kathryn Kalinak's observations on the purposes of film music, and David Neumeyer and James Buhler's debates on the emotional influence of soundtracks. The result suggests that "Himawari No Yakusoku" successfully utilizes important musical methods, including key selection, polyrhythm, thematic recapitulation, and harmonic resolution, to correspond with the emotional and narrative progressions of the film. The song begins with a warm tone in the key of Bb, the verses feature a polyrhythm that adds emotional complexity, the pre-chorus creates anticipation, and the chorus serves as a distinctive leitmotif. The instrumental portion adds introspective complexity, while the outro provides a gratifying conclusion. These features collectively improve the film's narrative, showcasing the song's essential function in influencing the audience's emotional and cognitive reactions.